Desain Pengendali Hybrid Fuzzy-SSMC Untuk Pengendalian Level Pada Coupled Tank - Dian Mursyitah; Ahmad Faizal; Ewi Ismaredah (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2019)
This study proposes level control in coupled tank systems. The behavior of level in coupled tank system does not reach the set point, when it is simulated in an open loop. The proposed controller is fuzzy logic. Fuzzy logic selected, because it does not require complicated mathematical calculations in terms of design when compared with other controllers. However, the outputs from fuzzy controllers with 3x3 rules base still lack in the response time. Furthermore, the SSMC controller was added to overcome these deficiencies. The addition of SSMC is expected to improve the lack of Fuzzy controllers. Based on the results of tests that have been carried out, it is proved that the combination of fuzzy and SSMC produces a fast output response and a minimum error with fast transient response. In tank 1, time constant is 0.36 seconds, rise time of 2.29 seconds, steady time of 5.66 seconds, delay time of 0.36 seconds. In tank 2, time constant is 0.66 seconds, the rise time is 1.52 seconds, the steady time is 5.66 seconds, the delay time is 0.36 seconds. The error are small, which are in tank 1 is -0.003 m3 and in tank 2 is -0.001 m3. The result is  hybrid fuzzy-SSMC controller that designed has worked well in improving system performance and being able to achieve the desired goals.